IDENTIFIKASI AVIFAUNA DI KAWASAN HUTAN KEMUNING KABUPATEN TEMANGGUNG - Akhyari, Annugrah Ilham; Permadani, Karunia Galih; Prajoko, Setiyo (FKIP Universitas Tanjungpura, 2024)
Forest is one of the wetland ecosystems that has a diversity of components in it. One of the biotic diversity that exists in forest areas is avifauna. This study aims to identify avifauna in the Kemuning Forest Area, Temanggung Regency, Central Java. Observations were made using the point count method and sampling using purposive sampling technique. The results showed that there were 27 bird species from 18 families. The birds found were mostly birds from the Passeriformes order because the observation location was a forest.